Enhancing the Visibility and Impact of Medical Conference Proceedings Through Abstract Publishing - Wadeia Sharief (Dubai Medical Journal)
The Dubai Medical Journal (DMJ) is introducing a special supplementary issue for abstracts from health-related scientific conferences, aiming to improve the visibility and impact of these proceedings. The DMJ enforces a structured abstract format (Introduction, Methodology, Results, Discussion (optional), and Conclusion) to align with Consolidated Standards of Reporting Trials (CONSORT) principles and improve research openness and accountability. A structured abstract format is necessary to increase the conversion rates to full papers and scholarly exposure. In addition, researchers perform bibliometric studies, allowing them to assess the visibility of these abstracts and the transfer rates from abstracts to full papers.